Trigonometry! #139

Calculus Level 3

For k Z + k\in Z^{+} , find the value of 0 π 2 sin 2 k x cot x d x \int_{0}^{\frac{\pi}{2}} \sin 2kx \cot xdx

Divide the answer by π \pi and enter.

This problem is part of the set Trigonometry .


The answer is 0.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Pi Han Goh
Jun 18, 2017

Let I ( k ) = 0 π / 2 sin ( 2 k x ) cot x d x \displaystyle I(k) = \int_0^{\pi /2} \sin(2kx) \cot x \, dx . We will attempt to prove that I ( k ) = π 2 I(k) = \dfrac{\pi}2 for k = 1 , 2 , 3 , k=1,2,3,\ldots .

Lemma 1: I ( 1 ) = π 2 I(1) = \dfrac{\pi}2 .

Proof: I ( 1 ) = 0 π / 2 sin ( 2 x ) cot x d x = 0 π / 2 2 sin x cos cos x sin x d x = 0 π / 2 2 cos 2 x d x = 0 π / 2 ( cos ( 2 x ) + 1 ) d x = π 2 I(1) = \int_0^{\pi/2} \sin (2x) \cot x \, dx =\int_0^{\pi/2} 2\sin x \cos \cdot \dfrac{\cos x}{\sin x} \, dx = \int_0^{\pi/2} 2\cos^2 x \, dx = \int_0^{\pi/2} (\cos(2x) + 1) \, dx = \dfrac{\pi}2 \qquad \blacksquare

Lemma 2: I ( k + 1 ) I ( k ) = 0 I(k+1) - I(k) = 0 for all k = 1 , 2 , 3 , k=1,2,3,\ldots .

Proof: For the equation below, we use apply the two trigonometric identities: sin ( A ) sin ( B ) = 2 cos ( A + B 2 ) sin ( A B 2 ) \sin(A) - \sin(B) = 2\cos\left(\dfrac{A+B}2 \right) \sin \left(\dfrac{A-B}2 \right) and 2 cos A cos B = cos ( A + B ) + cos ( A B ) 2\cos A \cos B = \cos(A+B) + \cos(A-B) .

I ( k + 1 ) I ( k ) = 0 π / 2 [ sin ( ( 2 k + 1 ) x ) sin ( 2 k x ) ] cot x d x = 0 π / 2 [ 2 cos ( ( k + 1 ) x ) sin x ] cos x sin x d x = 0 π / 2 2 cos ( ( k + 1 ) x ) cos x d x = 0 π / 2 [ cos ( ( 2 k + 2 ) x ) + cos ( 2 k x ) ] d x = 0 \begin{aligned} I(k + 1) - I(k) &=& \int_0^{\pi /2} \left [ \sin((2k+1)x) - \sin(2kx) \right ] \cot x \, dx \\ &=& \int_0^{\pi /2} \left [ 2\cos((k+1)x) \cdot \sin x \right ] \cdot \dfrac{\cos x}{\sin x}\, dx \\ &=& \int_0^{\pi /2} 2\cos((k+1)x) \cos x \, dx \\ &=& \int_0^{\pi /2} \left [ \cos((2k+2)x) + \cos(2kx) \right ] \, dx = 0 \qquad \blacksquare \end{aligned}

From Lemma 2, we know that 0 = I ( 2 ) I ( 1 ) = I ( 3 ) I ( 2 ) = I ( 4 ) I ( 3 ) = 0 = I(2) - I(1) = I(3) - I(2) = I(4) - I(3) =\cdots , thus I ( k ) = π 2 I(k) = \dfrac{\pi}2 . The answer is I ( k ) ÷ π = 0.5 I(k) \div \pi = \boxed{0.5} .

@Ankit Kumar Jain , here you go.

I first thought about solving this question via mathematical induction. I believed that there is another solution via Chebyshev polynomials or roots of unity , but I haven't worked it out yet (or haven't succeeded yet).

Pi Han Goh - 3 years, 12 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...